1965
DOI: 10.2466/pms.1965.21.2.431
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recognition of Tachistoscopically Presented English and Hebrew Words in Right and Left Visual Fields

Abstract: In this study, the role of lateral cerebral dominance in the consistent finding of lower tachistoscopic thresholds in the right than in the left visual field for alphabetic material was tested for readers of Hebrew and English. Twenty Israeli Ss were presented with Hebrew and English three-letter words, printed vertically, through a monocular tachistoscope, displaced to left or right of fixation by 2°21′. Ten American Ss were also tested for three-letter English words, under similar conditions. Significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…However, this difference was considerably weaker than in Experiment 1, where stimuli were presented horizontally (cf. Barton et al, 1965;Howell & Bryden, 1987;Lavidor et al, 2001;Mishkin & Forgays, 1952).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this difference was considerably weaker than in Experiment 1, where stimuli were presented horizontally (cf. Barton et al, 1965;Howell & Bryden, 1987;Lavidor et al, 2001;Mishkin & Forgays, 1952).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies wherein Hebrew or English words were presented in a vertical format still found a right visual field advantage (e.g., Barton, Goodglass, & Shai, 1965;Boles, 1985;Faust, Kravetz, & Babkoff, 1993), although the effect tended to be weaker than in the horizontal case and was sometimes not significant (Howell & Bryden, 1987). Reviewing the topic, Bradshaw, Nettleton, and Taylor (1981) concluded that word orientation does not seem to have much impact on visual field differences when single-syllable words are used (cf.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study with HebrewEnglish bilinguals, however, a RVF superiority was noted for words in both languages (Orbach, 1967). Barton, Goodglass and Shai (1965) examined the cerebral laterality effect in English-Hebrew bilinguals by presenting them with vertically printed English and Hebrew words. Both languages produced a RVF superiority, which was comparable to that obtained for English in monolingual group.…”
Section: Direction Of Scriptmentioning
confidence: 99%
“…Both languages produced a RVF superiority, which was comparable to that obtained for English in monolingual group. A control group of Hebrew-English bilinguals was not, however, tested (Barton et al, 1965). Finally, a study by Gaziel, examined the strength of the visual field preference in a group of Hebrew-English and EnglishHebrew bilinguals with different levels of proficiency in the second language.…”
Section: Direction Of Scriptmentioning
confidence: 99%